2010
DOI: 10.1002/gps.2621
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic associations of depression and apolipoprotein E genotype with incidence of dementia

Abstract: Objectives: A cohort study of Japanese-American men suggested interactive effects of depression and apolipoprotein E (APOE) e4 allele on risk of incident dementia. In another sample of East Asian origin, we sought to replicate the findings and to explore individual depressive symptoms where this interaction was most evident. Methods: Of 625 Korean community elders without dementia at baseline, 518 (83%) were followed over a 2.4-year period and were clinically assessed for incident dementia. Depression was iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 31 publications
2
24
0
1
Order By: Relevance
“…Recently, the synergistic effect of APOE ε4 allele and depressive symptoms on persistent cognitive deterioration was widely demonstrated in studies, including two with an East Asian sample (Kim et al, 2011; Niti et al, 2009). Structural studies further found hippocampal abnormalities in depressive patients with APOE ε4 allele that may contribute to AD conversion (Kim et al, 2002; Qiu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the synergistic effect of APOE ε4 allele and depressive symptoms on persistent cognitive deterioration was widely demonstrated in studies, including two with an East Asian sample (Kim et al, 2011; Niti et al, 2009). Structural studies further found hippocampal abnormalities in depressive patients with APOE ε4 allele that may contribute to AD conversion (Kim et al, 2002; Qiu et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19] On the basis of this observation, we have evaluated the ApoE genotypes and allelic distribution among a FMR1 premutation carrier cohort presenting with FXTAS. These data might contribute to uncover a new genetic risk factor for FXTAS and might be useful to identify new genes involved in the disease onset and progression.…”
Section: Original Research Articlementioning
confidence: 99%
“…[14][15][16] Although the pathogenic mechanism involving ApoE in these diseases is still unclear, it has been demonstrated that the ApoE ε4 allele is a well-established genetic risk factor for neurodegenerative disorders including Alzheimer disease (AD), Parkinson disease, and other disorders in which dementia is present. [17][18][19] On the basis of this observation, we have evaluated the ApoE genotypes and allelic distribution among a FMR1 premutation carrier cohort presenting with FXTAS. These data might contribute to uncover a new genetic risk factor for FXTAS and might be useful to identify new genes involved in the disease onset and progression.…”
Section: Original Research Articlementioning
confidence: 99%
“…50 A recent study demonstrated the presence of low CSF levels of cystatin C in patients with AD in comparison with healthy controls. 58 Although serum levels of cystatin C are presumably more related to renal dysfunction and CSF levels of cystatin C more to AD pathology, it is difficult to establish a one-to-one relationship due to intercorrelations.…”
Section: Discussionmentioning
confidence: 99%
“…33,36,[46][47][48][49][50][51][52][53][54][55][56][57][58][59][60] Two studies found no association (89% consistency). 61,62 Experts ranked diabetes as the second most important risk factor in both Delphi rounds.…”
Section: Diabetesmentioning
confidence: 99%